Konstruksi Media Dakwah: Tradisi Versus Ekonomi dalam Pemasaran Air Doa - Azhargany, Rojabi (Dakwah, 2021)
The phenomenon of marketing prayer water by offering blessings is a part of social relations accepted by the Indonesian people. This study aims to determine how blessings are accommodated in the practice of religious ritual therapy associated with certain religious figures. In particular, this study examines the practice of the Air Blessing (Holy Water) ritual of Habib Hasan Al Muhdor, a religious leader from the Shalawat Ahbabul Musthofa Council at Widoro Krejengan Probolinggo. To determine the community's construction of blessed water, data collection methods were used by observing and interviewing 1 assembly leader, 1 head of blessed water distribution and 3 local communities with special needs for blessed water, such as illness, pregnancy and life success. In analyzing the data, this study uses Berger's sacred canopy theory approach. As a result of observing this religious (or economic?) Therapy, society has transmitted material or money into blessings with the medium of Habib Muhdor's prayer water as a form of practice to get through life's problems. This fact shows the desecularization between the sacred and the profane, also shows the other side in practice it is used by certain figures for the purpose of strengthening patronage and capital capital. Keywords: Prayer Water, Blessing, Religious Therapy, Sacred World